Tissue xanthine oxidoreductase activity in a mouse model of aristolochic acid nephropathy. Issue 2 (1st February 2021) - Ishii, Takeo; Kumagae, Tomohiro; Wakui, Hiromichi; Urate, Shingo; Tanaka, Shohei; Abe, Eriko; Suzuki, Toru; Yamaji, Takahiro; Kinguchi, Sho; Kobayashi, Ryu; Haruhara, Kotaro; Nakamura, Takashi; et al.
Abstract : Xanthine oxidoreductase (XOR) is a critical enzyme in purine metabolism and uric acid production, and its levels are reported to increase during stress, thereby promoting organ damage. Herein, we investigated the activity of XOR in a mouse model of aristolochic acid I (AA)‐induced nephropathy, a type of nephrotoxic chronic kidney disease (CKD). A persistent decrease in renal function was observed in mice up to 4 weeks after 4 weeks of AA (2.5 mg kg −1 ) administration. Renal histology revealed an increase in tubular interstitial fibrosis over time. Although AA administration did not change XOR activity in the plasma, heart, liver, or muscle, XOR activity was persistently increased in renal tissue. Our results suggest that the renal tissue‐specific increase in XOR activity is involved in the progression of tubulo‐interstitial disorders, specifically fibrosis. Abstract : We investigated the activity of xanthine oxidoreductase (XOR) in a mouse model of aristolochic acid I (AA)‐induced nephropathy, a type of chronic kidney disease (CKD). After 4 weeks of AA (2.5 mg·kg −1 ) administration, renal histology revealed an increase in tubular interstitial fibrosis and XOR activity was persistently increased in renal tissue. Our data suggest that XOR activity is involved in the progression of tubulointerstitial disorders.